Failure analysis of superheater tubes in an air quenching cooler waste heat boiler. (January 2022) - Li, Yongjun; Chen, Hualin; Pan, Zhi; Liang, Hanzhao; Wang, Zhipeng; Feng, Zongjian; Li, Zhigang; Kuang, Yunkun
Highlights: The failure of superheater tubes in waste heat boiler was analyzed. No obvious wall thinning, swelling and mechanical damage were observed. The fracture surface showed the general intergranular brittle fracture. The failure mechanism of the tubes was identified as stress corrosion cracking. Abstract: The failure of superheater tubes in an air quenching cooler waste heat boiler from a cement plant is presented in this study. The tubes were composed of material specified to ASTM SA210C. After three months in service, one leak was detected in one of the tubes over its bent section. Subsequently, several leaks also were found in other tubes of the same boiler. In order to find out the root cause of the leaks, the failed tubes were investigated by visual inspection, optical emission spectroscopy, metallographic analysis, tensile test, micro-hardness measurements, and SEM/EDS analysis. Visual inspection revealed that no obvious wall thinning, swelling and mechanical damage were observed in the failure zone. The material met the chemical composition, microstructure, and tensile property requirements, while the micro-hardness far exceeded the requirements as specified by ASTM. It has been found that the fracture surfaces in general exhibited intergranular brittle fracture. Furthermore, the cracks with corrosion products originating on the water side of tubes were branched. According to finite element calculations, the residual stress in the failure zone due to bending confirmed that cracks propagated in a general direction perpendicular to the stresses. Therefore, the failure mechanism of the tubes was identified as stress corrosion cracking.